Frequency of Low Birth Weight in Patients with Gestational Hypertension: Frequency of Low Birth Weight - Farhan, Anum; Tariq, Sidra; Tasneem, Maria; Khan, Daniya; Chachar, Sanam; Baqai, Hamna Sabih; Fazal, Kamran (Pakistan Journal of Health Sciences, 2023)
Preterm birth and low birth weight are just two negative fetal outcomes that are linked to PIH. The WHO divides infants into three categories based on birth weight and gestational age: Small for gestational age, Appropriate for gestational age, and Large for gestational age. LBW babies are those who weigh less than 2.5kg within 24 hours of birth, according to these standards. Objectives: To determine the frequency of low birth weight in patients with gestational hypertension. Methods: This Descriptive study was done in department of Obstetrics and Gynecology unit III, Civil Hospital Karachi from 16th February 2019 to 15th August 2019. We enrolled 89women diagnosed with gestational hypertension meeting the criteria. Informed consent was taken. Results: Age range in this study was from 20 to 45 years with majority of the patients 52 (58.43%) were between 18 to 30 years of age. Mean gestational age was 39.51±2.7 weeks. Frequency of low birth weight in patients with gestational hypertension was found in 27 (30.34%) patients. Conclusions: This study concluded that frequency of low birth weight in patients with gestational hypertension is very high.